Recycling existing data: a greener future for clinical registries - Clive Weston (European Heart Journal - Quality of Care and Clinical Outcomes, 2018)
This article concerns the potential benefits of clinical disease registers, but points to the problems inherent in maintaining high quality reliable datasets. It comments on a recent (accompanying) paper from the West of Scotland that extracted data from existing administrative and clinical datasets to produce a meaningful registry.